RESPON BEBERAPA VARIETAS KEDELAI (Glycine max (L) Merril) TERHADAP KERAPATAN TANAM - Pramuja, Dimas; Rasyad, Aslim (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Soybean (Glycine max (L). Merril) is one of grain-producing crops which has high value of nutrition and has been cultivated in Indonesia since the 16th century. Soybean plays an  important role in human diet as alternative source of protein and oil. The aim of this research is to determine the response of soybean varieties on planting density and to determine the suitable planting space for specific varieties to be used in cultivating soybean. A field experiment was conducted using a randomized block design with 3 replications. The six varieties, ie; Argomulyo, Anjasmoro, Kaba, Burangrang, Gema, and Grobogan, were planted in a plot of 3 m long and 2 m wide  3 m with plant spacing of 40 cm x 20 cm, 40 cm x 15 cm, and 40 cm x 10 cm. The traits observed were plant height, leaf area, leaf area index, flowering date, harvest date, number of seeds per plant, seed weight per plant, seed yield per m2, and 100 seed weight. The results showed that except for leaf area and grain number per plant, most parameters observed varied among varieties. Soybean varieties grown with less  density had taller stem, smaller value of leaf area index and smaller seed size. The  magnitude values of most parameters were almost similar among planting densities indicating that planting density did not affect those characters. Keywords: Soybeans, Varieties, Plating space